Developing applications with Visual studio. NET - Grimes, Richard, 1964- (DevelopMentor series., 2002)
DEVELOPING APPLICATIONS WITH VISUAL STUDIO.NET is an in-depth guide that takes Windows programming to the next level: creating .NET applications that leverage the prior knowledge and experience of C++ Win32 programmers. The .NET Framework supplies programmers with rich standard run-time services, supports the development of Web-based services, and provides both inter-language and inter-machine interoperability. Programmers can now focus on creating more complex, more distributed, and more Web-enabled applications. This book begins by describing the .NET Framework, introducing the facilities .NET offers and the classes programmers can use. It goes on to describe the tools available in Visual Studio.NET and demonstrates their use. Readers are then ready to develop and debug applications with the help of clearly illustrated examples in C# and Managed C++. DEVELOPING APPLICATIONS WITH VISUAL STUDIO.NET covers commonly overlooked topics such as error handling, memory management, event logging, localization issues, performance monitoring, ATL Server, and Managed C++. Author Richard Grimes shares his hard-won understanding of Visual Studio.NET, emphasizing the innovations that save you time and trouble and steering you away from those that limit programming power. Among the topics explored in-depth: The Common Language Runtime (CLR) Core classes in the Framework Class Library Contexts and .NET remoting Interoperation and COM+ The Visual Studio.NET environment Creating and building solutions Visual C++.NET Application development Debugging With this book as your guide, you will learn how to efficiently develop strong, robust code within .NET.